Analisis Penyerapan Tenaga Kerja Pada Industri Menengah Dan Besar Se-Karesidenan Pekalongan Tahun 2008-2013 - Hasanah, Ulfa Fuadillah (2016)
This study titled analysis of employment in medium and large industries throughout the residency Pekalongan 2008 - 2013. The objective is to analyze the effect of output value, the number of business units and the level of wage increases on employment throughout the residency Pekalongan 2008 - 2013. The dependent variable in the form of the workforce (TK), while the independent variables such as output value (Q), the number of busi ness units (COMP) and the level of wages (W). This study uses secondary data with panel data regression analysis techniques. The results showed that the fixed effect model (FEM) is a panel data regression model is most appropriate. Based on the influence of the validation test or t test, the output value has no significant effect on employment, while the number of business units and wage levels significant positive effect on employment. Based on the test f, the output value, the number of business units an d wage levels simultaneously or together have an effect on employment